The human microbiome: A promising target for lung cancer treatment - Sun, Ying; Wen, Miaomiao; Liu, Yue; Wang, Yu; Jing, Pengyu; Gu, Zhongping; Jiang, Tao; Wang, Wenchen (Frontiers in Immunology, 2023)
Lung cancer is the leading cause of cancer-related deaths worldwide, and insights into its underlying mechanisms as well as potential therapeutic strategies are urgently needed. The microbiome plays an important role in human health, and is also responsible for the initiation and progression of lung cancer through its induction of inflammatory responses and participation in immune regulation, as well as for its role in the generation of metabolic disorders and genotoxicity. Here, the distribution of human microflora along with its biological functions, the relationship between the microbiome and clinical characteristics, and the role of the microbiome in clinical treatment of lung cancer were comprehensively reviewed. This review provides a basis for the current understanding of lung cancer mechanisms with a focus on the microbiome, and contributes to future decisions on treatment management.